The relationship between frontal plane trunk control during landing and lower extremity muscle strength in young athletes after anterior cruciate ligament reconstruction - Fryer, C.; Ithurburn, M. P.; McNally, M. P.; Thomas, S.; Paterno, M. V.; Schmitt, L. C. (Clinical Biomechanics, 2019)
Background: Lower extremity landing asymmetries are common and associated with strength deficits after anterior cruciate ligament reconstruction. However, less is known regarding trunk control during landing. This study's hypotheses were that frontal plane trunk excursion during single-leg landing would be greater in young athletes after anterior cruciate ligament reconstruction compared to controls and would be associated with strength deficits. Methods: Participants included 130 young athletes recently cleared for return-to-sport following anterior cruciate ligament reconstruction and 56 uninjured young athletes. Frontal plane trunk excursion was quantified using three-dimensional motion analysis during a single-leg landing task. Quadriceps and hip abduction strength were measured using an isokinetic dynamometer. Frontal plane trunk excursion was compared between the anterior cruciate ligament reconstruction and control groups and among quadriceps strength subgroups using independent t-tests and one-way analysis of variance. Linear regression examined the association between frontal plane trunk excursion and strength measures in the anterior cruciate ligament reconstruction group. Findings: The anterior cruciate ligament reconstruction group demonstrated greater frontal plane trunk excursion compared to controls. The low-quadriceps group demonstrated greater frontal plane trunk excursion compared to both the high-quadriceps and control groups. Additionally, the high-quadriceps group demonstrated greater frontal plane trunk excursion compared to controls. In the anterior cruciate ligament reconstruction group, lower quadriceps and hip abduction strength were weakly associated with greater frontal plane trunk excursion. Interpretation: Young athletes at time of return-to-sport after anterior cruciate ligament reconstruction demonstrated increased frontal plane trunk excursion during single-leg landing. Additionally, increased frontal plane trunk excursion was weakly associated with strength deficits.